Effectiveness of Chamomile and Ginger on Reducing Pain Intensity in Active Phase I Partus - Joharmi Joharmi; Herviza Wulandary Pane; Ustifina Hasanah; Raudha Raudha (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
Aromatherapy is a method that uses essential compounds to improve physical, emotional, and spiritual health. Another effect is to reduce pain and anxiety. Several studies have demonstrated the effectiveness of aromatherapy for pain and stress in maternity patients. Chamomile is one of the herbal medicinal plants that has long been known in human life. Chamomile that has been processed is generally used to treat diseases experienced by humans, namely fever, inflammation, muscle spasms, menstrual disorders, insomnia, wounds, digestive disorders, rheumatic pain, and hemorrhoids. Chamomile oil is used extensively in cosmetics and aromatherapy. Many chamomile treatments can be developed; the most famous medicine is chamomile herbal aromatherapy. This study used a posttest-only control group design with 44 respondents, all pregnant women whose gestational age was between 38-41 weeks.The results of therapy in the form of a decrease in pain in the chamomile oil therapy group compared to the ginger group turned out to have a significant difference. The pain intensity of some respondents before ginger therapy was moderate pain, namely, 12 people (54%) and mild pain, 10 people (46%). After ginger therapy, the pain intensity of respondents experienced no pain, namely as many as 10 people (46%), mild pain in as many as 7 people (32%), and moderate pain in as many as 5 people (22%).Value < 0.05, whereas with ginger, the p-value was 0.049, also the p-value < 0.05, it can be interpreted that chamomile and ginger are both effective in reducing the intensity of labor pain during the active phase I stage, but chamomile is more effective compared to ginger, because the smaller the p-value, the greater the effectiveness, as shown in the table above. There is a significant difference between chamomile and ginger oil in reducing pain.